Acute respiratory distress syndrome in a case of diabetic ketoacidosis requiring ECMO support. (7th July 2021) - Darrat, Milad; Gilmartin, Brian; Kennedy, Carmel; Smith, Diarmuid
Abstract : Summary: Acute respiratory distress syndrome (ARDS) is a rare but life-threatening complication of diabetic ketoacidosis (DKA). We present the case of a young female, with no previous diagnosis of diabetes, presenting in DKA complicated by ARDS requiring extra corporeal membrane oxygenation (ECMO) ventilator support. This case report highlights the importance of early recognition of respiratory complications of severe DKA and their appropriate management. Learning points: ARDS is a very rare but life-threatening complication in DKA. The incidence of ARDS remains unknown but less frequent than cerebral oedema in DKA. The mechanism of ARDS in DKA has multifactorial aetiology, including genetic predisposition. Early recognition and consideration of rare pulmonary complication of DKA can increase survival rate and provide very satisfactory outcomes. DKA patients who present with refractory ARDS can be successfully rescued by ECMO support.